Value relevance of accounting numbers for valuation / Muliati Aba Ibrahim - Ibrahim, Muliati Aba (2004)
Recent empirical work suggested that the ability of accounting numbers to explain the relationship between accounting numbers and stock prices over the past four decade [Collins, Maydew and Weiss [1997]; Francis and Schipper [1999]; and Lev and Zarowin [1999]] has deteriorated. This provide the key motivation for this study to examine the relationship between accounting numbers and stock price in the Malaysian emerging capital market which is useful for firm valuation. The findings of this study suggest that the accounting earnings and book value are capturing most of the information that is relevant to assess the values of firms and at the same time, it also suggests a decline in their value relevance after the financial crisis period. The results also suggest that accounting earnings and book value as well as non-accounting beta are more valued during the financial crisis period as compared to the after-effect of the financial crisis period. Overall, the accounting estimate of the value of the firm is not deviating from the markets’ estimate, which indicates that accounting numbers continues to play the central role in the determination of stock prices.